Percepción de estrés, autoeficacia en el cuidado y estilo de crianza del cuidador principal de niños con diagnostico del trastorno del espectro autista (2017)
The relationship between Parental Stress, Parental perception of care, and parenting styles in primary caregivers of children diagnosed with Autistic Spectrum Disorder (ASD) between 2 and 13 years of age was analyzed. To the total sample of 25 primary caregivers of children with ASD, three tests were applied: the Autism Parenting Scale (APSI) for the stress variable, KIPP (Kansas Inventory of Parental Perceptions) for the parental perceptions variable, and one parenting questionnaire to measure authoritarian, democratic and permissive parenting styles. For the comparative analysis, the sample was divided into two groups depending on the year of diagnosis. Data was analyzed using Spearman correlations and the median test for independent samples. In the results of this research it can be observed that there are no significant differences between stress, parenting style and self-perception of care when comparing the two groups...